What yeast and cardiomyocytes share: ultradian oscillatory redox mechanisms of cellular coherence and survival - Lloyd, David (2011)
The coherent and robust, yet sensitively adaptable, nature of organisms is an astonishing phenomenon that involves massive parallel processing and concerted network performance at the molecular level. Unravelling the dynamic complexities of the living state underlines the essential operation of ultradian oscillations, rhythms and clocks for the establishment and maintenance of functional order simultaneously on fast and slower timescales. Non-invasive monitoring of respiration, mitochondrial inner membrane potentials, and redox states (especially those of NAD(P)H, flavin, and the monochlorobimane complex of glutathione), even after more than 50 years research, continue to provide both new insights and biomedical applications. Experiments with yeast and in cardiac cells reveal astonishing parallels and similarities in their dynamic biochemical organization.